Age of onset of cerebral venous thrombosis: the BEAST study. (March 2023) - Ranjan, Redoy; Ken-Dror, Gie; Martinelli, Ida; Grandone, Elvira; Hiltunen, Sini; Lindgren, Erik; Margaglione, Maurizio; Le Cam Duchez, Veronique; Bagan Triquenot, Aude; Zedde, Marialuisa; Mancuso, Michelangelo; Ruigrok, Ynte M; et al.
Background: Cerebral venous thrombosis (CVT) is an uncommon cause of stroke in young adults. We aimed to determine the impact of age, gender and risk factors (including sex-specific) on CVT onset. Methods: We used data from the BEAST (Biorepository to Establish the Aetiology of Sinovenous Thrombosis), a multicentre multinational prospective observational study on CVT. Composite factors analysis (CFA) was performed to determine the impact on the age of CVT onset in males and females. Results: A total of 1309 CVT patients (75.3% females) aged ⩾18 years were recruited. The overall median (IQR-interquartile range) age for males and females was 46 (35–58) years and 37 (28–47) years ( p  < 0.001), respectively. However, the presence of antibiotic-requiring sepsis ( p  = 0.03, 95% CI 27–47 years) among males and gender-specific risk factors like pregnancy ( p  < 0.001, 95% CI 29–34 years), puerperium ( p  < 0.001, 95% CI 26–34 years) and oral contraceptive use ( p  < 0.001, 95% CI 33–36 years) were significantly associated with earlier onset of CVT among females. CFA demonstrated a significantly earlier onset of CVT in females, ~12 years younger, in those with multiple (⩾1) compared to '0' risk factors ( p  < 0.001, 95% CI 32–35 years). Conclusions: Women suffer CVT 9 years earlier in comparison to men. Female patients with multiple (⩾1) risk factors suffer CVT ~12 years earlier compared to those with no identifiable risk factors.